Early branching arbuscular mycorrhizal fungus Paraglomus occultum carries a small and repeat-poor genome compared to relatives in the Glomeromycotina. Issue 4 (22nd April 2022) - Malar C, Mathu; Wang, Yan; Stajich, Jason E.; Kokkoris, Vasilis; Villeneuve-Laroche, Matthew; Yildirir, Gokalp; Corradi, Nicolas
Abstract : The arbuscular mycorrhizal fungi (AMFs) are obligate root symbionts in the subphylum Glomeromycotina that can benefit land plants by increasing their soil nutrient uptake in exchange for photosynthetically fixed carbon sources. To date, annotated genome data from representatives of the AMF orders Glomerales, Diversisporales and Archaeosporales have shown that these organisms have large and highly repeated genomes, and no genes to produce sugars and fatty acids. This led to the hypothesis that the most recent common ancestor (MRCA) of Glomeromycotina was fully dependent on plants for nutrition. Here, we aimed to further test this hypothesis by obtaining annotated genome data from a member of the early diverging order Paraglomerales ( Paraglomus occultum ). Genome analyses showed this species carries a 39.6 Mb genome and considerably fewer genes and repeats compared to most AMF relatives with annotated genomes. Consistent with phylogenies based on ribosomal genes, our phylogenetic analyses suggest P. occultum as the earliest diverged branch within Glomeromycotina. Overall, our analyses support the view that the MRCA of Glomeromycotina carried hallmarks of obligate plant biotrophy. The small genome size and content of P. occultum could either reflect adaptive reductive processes affecting some early AMF lineages, or indicate that the high gene and repeat family diversity thought to drive AMF adaptability to host and environmental change was not an ancestral feature of these prominent plant symbionts.